Gender-based violence, law, and African society - Raufu, Abiodun; Olomola, Omolade; Mendie, Edidiong (Lexington Books, 2023)
"This book offers contemporary perspectives on the different forms of gender-based violence in Africa through a legal, cultural, and sociological lens"--